2017
DOI: 10.1002/oa.2625
|View full text |Cite
|
Sign up to set email alerts
|

How Short Is Short, and Why? A Probable Case of Proportionate Dwarfism From Egypt's Third Intermediate Period in the Dakhleh Oasis, Egypt

Abstract: This study describes a probable proportionate dwarf from a Third Intermediate Period cemetery at Ain Tirghi in the Dakhleh Oasis, Egypt. The skeleton (Burial 22 or B22) is an adult woman estimated to be in her mid-to-late thirties. Most medical literature defines an adult stature of 2 standard deviations below the population mean as an indicator for clinically short stature, with some bioarchaeologists and clinicians identifying severe short stature at 3 standard deviations below the population mean. B22 satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Body size and other factors were not accounted for here because the material was excavated from the same geographic region and represent individuals of the same population, which lived at the same time, under the same environmental conditions. Supporting this determination, anthropological studies of stature and limb proportions in workers and high officials have indicated that these two groups of ancient Egyptians represent one population, with no significant differences in body size (Azab, 2000;Molto & Kirkpatrick, 2018). Individuals with obvious pathological deformities that might affect their physical activity, bone morphology, or EC appearance were excluded as well.…”
Section: Determination Of Sex and Agementioning
confidence: 99%
“…Body size and other factors were not accounted for here because the material was excavated from the same geographic region and represent individuals of the same population, which lived at the same time, under the same environmental conditions. Supporting this determination, anthropological studies of stature and limb proportions in workers and high officials have indicated that these two groups of ancient Egyptians represent one population, with no significant differences in body size (Azab, 2000;Molto & Kirkpatrick, 2018). Individuals with obvious pathological deformities that might affect their physical activity, bone morphology, or EC appearance were excluded as well.…”
Section: Determination Of Sex and Agementioning
confidence: 99%
“…Since bicondylar length measures contribution to stature it is more highly correlated with stature. Differences between T17 and the female reference population (n = 9, coming from the same layer of the Piazza XX Settembre necropolis) was assessed using standard deviations from a normal distribution (Molto and Kirkpatrick, 2018). For each long bone, z-scores were calculated to assess to which comparative group T17 was closest (Hernandez, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The calculated stature of T17, along with the archaeo-anthropological comparison and comparison with the Modena site female population mean heights support the case for dwarfism. Clinical literature defines a variation of three standard deviations below the sex-specific adult population mean as the criterion to diagnose clinically short stature (Bleuze et al, 2014;Hunter and Rosenfeld, 1997;Molto and Kirkpatrick, 2018;Waldron, 2009). T17 is at least three stan dard deviations below the adult female population mean for the length measurements of the humeri, ulnae, femora, tibiae, and fibulae (Table 3) and the summed measurements of humeri/radii and femora/tibiae (Table 4).…”
Section: Diagnostic Criteria For Pathological Short Staturementioning
confidence: 99%
“…In the past, evidence from artistic, archaeological, epigraphic, ethnographic, and osteological materials on disproportionate dwarfism was documented from both skeletal remains and material culture depictions during various periods throughout the world from ancient populations of Egypt (Kozma, 2006(Kozma, , 2008Molto & Kirkpatrick, 2018), the Near East (Slon et al, 2013), Europe (Arcini & Frölund, 1996;Bianucci et al, 2012;Dasen, 1988Dasen, , 1990Dasen, , 1993Frayer et al, 1988;Garcia & Santos, 2020;Gladykowska-Rzeczycka, 1980;Minozzi et al, 2013;Nater et al, 2016;Sables, 2010;Traversaria et al, 2020;Waters-Rist & Hoogland, 2013), Asia (Halcrow et al, 2020;Woo et al, 2015), Latin America (Miller, 1985;Rodríguez et al, 2012), South America (Pachajoa et al, 2009;Rodríguez et al, 2012), and North America (Cormier & Buikstra, 2017;Hoffman, 1976). The earliest case of achondroplasia was found in late Paleolithic tombs in Italy, the remains of an adolescent male named "Romito 2" (Frayer et al, 1988).…”
Section: Introductionmentioning
confidence: 99%